Opowieści o końcu świata. Medialne wizerunki sekty proroka Ilji z Wierszalina (Przegląd Religioznawczy – The Religious Studies Review, 2022)
The article is dedicated to Eliasz Klimowicz (1864–1939/1941), the creator of the sect from Wierszalin. Using a theoretical framework based on the dichotomy of the sacred – profane, an attempt was made to analyze the media image of the propeth Ilya and his followers hathered around him. A fictional film Historia o proroku Eliaszu z Wierszalina and other audiovisual material were made about the sect, analyzed in this study.